FGF-2 is bound to perlecan in the pericellular matrix of articular cartilage, where it acts as a chondrocyte mechanotransducer. - Vincent, T; McLean, C; Full, L; Peston, D; Saklatvala, J (2007)
OBJECTIVE: We have shown previously that cutting or loading articular cartilage resulted in a fibroblast growth factor-2 (FGF-2) dependent activation of the extracellularly regulated kinase (ERK), and induction of a number of chondrocyte regulatory proteins including tissue inhibitor of metalloproteinase-1 and matrix metalloproteinases 1 and 3. An extracellular matrix-bound pool of FGF-2 was apparent, which could be liberated from the tissue by heparitinase (Vincent et al., Proc Natl Acad Sci U S A 2002;99(12):8259-64, Vincent et al., Arthritis Rheum 2004 Feb;50(2):526-33). Our objectives were to determine where FGF-2 was stored in articular cartilage, to which proteoglycan it was bound, and to elucidate its role in chondrocyte mechanotransduction. METHODS: Immunohistochemistry and confocal microscopy were used to localise FGF-2 in the tissue. In vitro binding studies were performed using IASYS surface plasmon resonance. To study the role of pericellular FGF-2 in mechanotransduction cartilage explants or articular chondrocytes encapsulated in alginate were loaded using an in house loading rig. The loading response was assessed by the activation of ERK, in the presence or absence of a specific FGFR inhibitor. RESULTS: Here we have identified perlecan as the heparan sulphate proteoglycan that sequesters FGF-2 in articular cartilage. Perlecan and FGF-2 co-localised within the type VI collagen-rich pericellular matrix of porcine and human articular cartilage. Chondrocytes encapsulated in alginate were able to accumulate pericellular perlecan and FGF-2 in culture, and deliver an FGF-dependent activation of ERK when loaded. CONCLUSION: Loading-induced ERK activation was dependent upon the presence and concentration of pericellular FGF-2, suggesting a functional role for this matrix-bound growth factor in chondrocyte mechanotransduction.